Socio-emotional Development in Children with Physical Impairment - Cahyani, Atika Dwi; Widyastuti; Affandi, Ghozali Rusyid (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to provide an overview of the socio-emotional development of children with physical impaiment and the factors that influence the socio-emotional development of children with physical impairment. This study used qualitative case studies with 3 subjects aged 6-14 years old with physical impairment at SDLB Al-Chusnaini Sukodono and 5 significant others. Data collection methods used are interviews that are equipped with interview guidelines and observations. Data analyzed using Miles and Huberman qualitative data analysis which include data reduction, data display, and data verification. The results of this study indicate that among the three subjects, two subjects showed that they had socio-emotional development in accordance with their age and one subject who had socio-emotional development that was not in accordance with his age. Factors that influence socio-emotional development in each subject include pleasant environmental factors, family environmental factors, environmental factors that provide stimulation, emotional satisfaction factors, responsibility burden factors, as well as methods of educating children, and application of religious values